2020
DOI: 10.1101/2020.09.05.20188821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnicity and clinical outcomes in COVID-19: A Systematic Review and Meta-analysis

Abstract: Importance The association of ethnicity with outcomes in patients with COVID-19 is unclear. Objective To determine whether the risk of SARS-CoV-2 infection, COVID-19 intensive care unit (ICU) admission and mortality are associated with ethnicity. Data Sources We searched all English language articles published 1st December 2019 - 30th June 2020 within MEDLINE, EMBASE, PROSPERO and the Cochrane library using indexing terms for COVID-19 and ethnicity, as well as manuscripts awaiting peer review on MedRxiv dur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 66 publications
(39 reference statements)
2
123
1
Order By: Relevance
“…As noted by others (e.g., Luchetti et al, 2020 ), studies suggesting resilience to loneliness during the pandemic have not included these populations. Moreover, there is evidence that certain minority groups are experiencing worse physical health effects of Covid-19 ( Sze et al, 2020 ), but the work presented in this special section does not yet systematically consider variability in psychological processes across race and ethnicity.…”
Section: Putting the Findings In Perspectivementioning
confidence: 99%
“…As noted by others (e.g., Luchetti et al, 2020 ), studies suggesting resilience to loneliness during the pandemic have not included these populations. Moreover, there is evidence that certain minority groups are experiencing worse physical health effects of Covid-19 ( Sze et al, 2020 ), but the work presented in this special section does not yet systematically consider variability in psychological processes across race and ethnicity.…”
Section: Putting the Findings In Perspectivementioning
confidence: 99%
“…The COVID-19 pandemic has also disproportionately affected those from ethnic minority groups, with previous work demonstrating an increased risk of SARS-CoV-2 infection and adverse outcome relative to White individuals. 5,11,12 Furthermore, HCWs of minority ethnicity have been shown to be at higher risk of infection than their White colleagues. 9,13 In light of the increased risk of COVID-19 infection and adverse outcome faced by ethnic minority HCWs, concerns have been raised regarding uptake of the SARS-CoV-2 vaccine in this group both in the UK and in US 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest signi cantly higher worry level among populations residing outside Europe, and in some racial and ethnic communities (Asian, Black, Latin/Hispanic, Mixed Race, South Asian and other). Several factors likely contribute to this result including: 1) differences in access and quality of health care among regions (many of the highest-ranking health care systems are found in Europe); 2) the impact being able to access health care can have upon feelings of wellbeing and health and; 3) consistently established differences in COVID-19 outcomes between racial and ethnic groups (35). At the same time, our model found that having access to health insurance, a proxy for accessible health care, was not associated with worry level.…”
Section: Discussionmentioning
confidence: 99%